A Comment on "A direct approach for determining the switch soints in the Karnik-Mendel algorithm" - Chen, Chao; Wu, Dongrui; Garibaldi, Jonathan M.; John, Robert; Twycross, Jamie; Mendel, Jerry (IEEE, 2018)
This letter is a supplement to the previous paper “A Direct Approach for Determining the Switch Points in the Karnik-Mendel Algorithm”. In the previous paper, the enhanced iterative algorithm with stop condition (EIASC) was shown to be the most inefficient in R. Such outcome is apparently different from the results in another paper in which EIASC was illustrated to be the most efficient in Matlab. An investigation has been made into this apparent inconsistency and it can be confirmed that both the results in R and Matlab are valid for the EIASC algorithm. The main reason for such phenomenon is the efficiency difference of loop operations in R and Matlab. It should be noted that the efficiency of an algorithm is closely related to its implementation in practice. In this letter, we update the comparisons of the three algorithms in the previous paper based on optimised implementations under five programming languages (Matlab, R, Python, C and Java). From this, we conclude that results in one programming language cannot be simply extended to all languages.